2020
DOI: 10.3390/ma13092153
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nano-Fibers for Biomedical and Tissue Engineering Applications: A Comprehensive Review

Abstract: Pharmaceutical nano-fibers have attracted widespread attention from researchers for reasons such as adaptability of the electro-spinning process and ease of production. As a flexible method for fabricating nano-fibers, electro-spinning is extensively used. An electro-spinning unit is composed of a pump or syringe, a high voltage current supplier, a metal plate collector and a spinneret. Optimization of the attained nano-fibers is undertaken through manipulation of the variables of the process and formulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 224 publications
(235 reference statements)
0
82
0
1
Order By: Relevance
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that PMMA-based BCs cannot form covalent bonds with the natural bone, and a lack of interactions may induce implant loosening after a while. According to the results, the addition of CNTs, GO, and carbon-based composites [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ] can enhance the setting times, temperature, strength, bioactivity, and cellular activity of the PMMA-based BCs. However, it is believed that utilization of GO could have further impact than CNTs reinforcing agents on enhancement of the strength and durability of PMMA-based BCs, conquering the potential issue presented by premature failure of the implant.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that we are still a great distance from organ printing. Even though recent deposition and manufacturing systems permit us to develop structures similar to tissue in their composition, the progression of entirely functioning tissue is a much more significant step [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Limitations Advantages and Future Prospects Of Alg 3d Prmentioning
confidence: 99%
“…Nevertheless, restricted materials with appropriate printability, stability of construct in SBF and mechanical characteristic continue to be the serious challenges that have to be conquered prior to extensive designing for products manufacturing in biomedical fields. It is worth noting that the electro-spinning approach has gained considerable attention from biomedical experts all around the world for manufacturing various polymers, particularly CS-based polymer scaffolds loaded with drugs for biomedical and wound dressing purposes [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ]. Application of CS-based biopolymers through 3D [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ] printing for biomedical purposes especially as bio-ink in an effort to fabricate complex tissues will probably be an upcoming pattern of 3D printing materials progression.…”
Section: Benefits Limitations and Future Prospectsmentioning
confidence: 99%